Rhinocerebral mucormycosis secondary to severe acute pancreatitis and diabetic ketoacidosis: a case report - Jinjing Wang; Yao Li; Shuai Luo; Hong Zheng (BMC, 2021)
Abstract Introduction Rhinocerebral mucormycosis is a rare and severe form of opportunistic fungal infection that can develop rapidly and cause significant mortality, particularly among diabetic patients suffering from ketoacidosis. Diagnosing rhinocerebral mucormycosis during the early stages of infection is challenging. Case presentation We describe a case of rhinocerebral mucormycosis secondary to severe acute pancreatitis in a patient suffering from diabetic ketoacidosis. In this case, the condition was not diagnosed during the optimal treatment window. we therefore provide a thorough overview of related clinical findings and histopathological characteristics, and we discuss potential differential diagnoses. Conclusions In summary, we described a case of rhinocerebral mucormycosis secondary to severe acute pancreatitis in a patient suffering from diabetic ketoacidosis, with the optimal treatment window for this condition having been missed. This report suggests that a definitive mucormycosis diagnosis can be made based upon tissue biopsy that reveals the presence of characteristic hyphae. Early diagnosis and treatment are essential in order to improve patient prognosis.